Analisis Berbagai Faktor Yang Dipertimbangkan Dalam Melakukan Segmentasi Pasar Berdasarkan Benefit Dan Preferensi Pada Perusahaan Asuransi di Malang - Triatmanto, Boge (Fakultas Ekonomi, UIN Maliki Malang, 2010)
Objective of the research is to find out the considered factor for market segmentation at the insurance company in Malang based on benefit and preference approaches. Data analysis used factor analysis in order to find out any considered factors in performing market segmentation based on benefit and preference approaches. Result of the research shows five dimensions or factor, which are considered in performing market segmentation based on benefit and preference approaches of the customers at the insurance company in Malang. Those factors are is as fellow experiences of the company, product utility, varieties of the product, services and income. Result implication of the research for the insurance company in Malang shows that the segmentation should be directed to customers who pay more attention an reliability of the company and customers who look for utility of the insurance product as well as customers who get wage from side jobs in addition to monthly pay.